THE GENDER GAP IN BANK CREDIT ACCESS: THE CASE OF SMALL FIRMS - Monika Jukić; Vlatka Škokić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The aim of the paper is to determine whether there is a gender gap in bank credit access among male and female entrepreneurs. In addition, the paper also investigates the differences between male and female entrepreneurs when obtaining a loan to start a business. The study is based on qualitative preliminary research among small entrepreneurs in Croatia, who requested a bank loan, regardless of whether it was rejected or approved. The results show that there is no gender gap in bank credit access. In addition, the results did not observe any differences between male and female entrepreneurs in terms of loan conditions. The problem of banks’ aversion to risk, and thus to the financing of the small firms in Croatia, has been replaced by the role of the Croatian bank for reconstruction and development (HBOR). The results confirm that the model of cooperation between HBOR and commercial banks strongly encourages lending to female entrepreneurs. Finally, results show that female entrepreneurs respond to and engage in different support and educational programs, compared to their male counterparts.